Trump Ante Portas: Political Polarization Undermines Rule-Following Behavior - Christoph Feldhaus; Lukas Reinhardt; Matthias Sutter (Institute of Labor Economics (IZA), 2024)
In a democracy, it is essential that citizens accept rules and laws, regardless of which party is in power. We study why citizens in polarized societies resist rules implemented by political opponents. This may be due to the rules' specific content, but also because of a general preference against being restricted by political opponents. We develop a method to measure the latter channel. In our experiment with almost 1,300 supporters and opponents of Donald Trump, we show that polarization undermines rule-following behavior significantly, independent of the rules' content. Subjects perceive the intentions behind (identical) rules as much more malevolent if they were imposed by a political opponent rather than a political ally.
Keywords: C91; D90; D91; 330; political polarization; social identity; outgroup; economic preferences; experiment